THE PREVALENCE OF ALLERGIC DISEASES IN CHILDREN AND THE EFFECTIVENESS OF IMMUNOTHERAPY METHODS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review highlights the growing prevalence of allergic diseases among children, now affecting 25-30% of the pediatric population globally. It discusses key allergic conditions such as asthma, allergic rhinitis, atopic dermatitis, and food allergies, which have shown a marked increase in recent decades. The article emphasizes the role of allergen-specific immunotherapy-including subcutaneous and sublingual methods-as an effective, disease-modifying treatment. Recent clinical trials show that immunotherapy can lead to long-term remission in 70-85% of well-selected pediatric patients. The importance of early intervention during key developmental stages is also underscored, as it improves outcomes and may prevent progression of the allergic march. The review concludes with evidence-based recommendations to enhance the effectiveness of immunotherapy in pediatric clinical practice.